A Comprehensive Hepatitis B Surface Antigen-Positive Patient-Centered Screening and Linkage to Care Strategies Targeting Microelimination of Hepatitis C Virus Infection in Chongqing, China - Dachuan Cai; Dazhi Zhang; Peng Hu; Hong Ren (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. The likelihood of coinfection increases in regions where HBV is endemic because of the similar transmission route. China is another endemic nation, with 5.9% of the population being HBsAg-positive. This study aimed to evaluate the prevalence of HCV antibody positivity in HBsAg-positive subjects, HCV RNA positivity in anti-HCV positive subjects, and HBV/HCV coinfection with the hope of exploring hepatitis C microelimination using currently available therapies. Method. 12,500 HBsAg-positive serum samples were collected. All samples were screened for anti-HCV. Furthermore, positive samples were screened for HCV RNA. All patients with positive HCV RNA were followed up for suspicious transmission routes of HCV and linkage to care. Results. 44 out of 10,560 (0.4%) patients with positive HBsAg had detectable anti-HCV. There were 32 males and 12 females, with a statistical difference. 17 out of 44 were HCV RNA positive. Among them, 15 out of 38 patients were HCV RNA positive; 8 patients had started anti-HCV treatment with the DAA regimen, while the other 7 patients had not. After patient education, one patient had begun treatment and reached SVR12, while three patients still refused anti-HCV treatment. Conclusion. The HCV/HBV coinfection prevalence was found to be lower in this study. Even though HBV and HCV share a somewhat similar transmission route, HBsAg-positive subjects may not be at high risk for HCV infection. The process of hepatitis C’s microelimination could be accelerated by increasing patient awareness and education. This trail is registered with NCT03794791.